Transformasi Pembelajaran Kewirausahaan: Mengasah Kreativitas Siswa melalui Project Based Learning - Rahmawati, Rani; Sujaya, Krisna; Yusup, Ismail (Nusantara: Jurnal Pendidikan Indonesia, 2024)
Purpose – This research is the background of the low creative thinking skills of class XII TKJ in PKK subjects at SMKN Sukaresik. This study aimed to determine the differences in creative thinking skills of experimental class students who applied the project-based learning model with the control class who used the conventional model.Method – The model used in this research is a quasi-experiment with Nonequivalent Control Group Design. Data collection techniques in this study were questionnaires through pretest and posttest, observation, and documentation. The data analysis techniques consist of descriptive analysis, normality test, homogeneity test, independent sample t-test, and N-Gain test.Findings – The results of the data analysis showed that the sig value (two-sided p) < 0.001 and it is smaller than 0.005, so there is a significant difference in the creative thinking ability of the experimental class using the project-based learning model with the control class using the conventional model. Based on the n-gain value of 0.75, the project-based learning model is proven to be better at improving creative thinking skills. Research Implications – The impact of this research is to provide references to teachers in determining the proper learning model to apply in PKK learning. Teachers must build a learning environment that can stimulate learners' creativity. One of these efforts is embracing learners to be directly involved in the learning process through group discussions, collaborative projects, or presentations.